2023
DOI: 10.1186/s12913-023-10111-8
|View full text |Cite
|
Sign up to set email alerts
|

One-year healthcare costs after robotic-assisted and laparoscopic partial and radical nephrectomy: a cohort study

Kennedy E. Okhawere,
Gediwon Milky,
Shirin Razdan
et al.

Abstract: Objective Despite the wide-spread adoption of robotic-assisted surgery (RAS), the cost–benefit implications for partial (PN) and radical nephrectomy (RN) versus laparoscopic surgery (Lap) is not well established. We sought to examine the trend of adoption and 1-year healthcare expenditure of PN and RN, and compare 1-year expenditures of RAS versus Lap for PN and RN. Patients and methods This cohort study used the MerativeTM MarketScan® Databases be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This trend underscores the multifaceted influences affecting surgical choices. Several studies based on different databases revealed that the advent of robotic and laparoscopic surgeries has significantly enhanced the application of PN ( 49 54 ). These minimally invasive approaches have been pivotal in refining the procedure's efficacy and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This trend underscores the multifaceted influences affecting surgical choices. Several studies based on different databases revealed that the advent of robotic and laparoscopic surgeries has significantly enhanced the application of PN ( 49 54 ). These minimally invasive approaches have been pivotal in refining the procedure's efficacy and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Data about individual patients are integrated from all care settings (eg, inpatient, outpatient, and outpatient pharmacy), maintaining health care use and cost record connections at the patient level. MarketScan reports the payments that came on the paid claims submitted by various insurance carriers and provides data about total payments (total costs to all payers) and payments made by patients (OOP costs) for their coinsurance, copayment, and/or deductible . We identified enrollees aged 18 to 45 years with at least 1 full year of continuous enrollment from January 1, 2010, to December 31, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…MarketScan reports the payments that came on the paid claims submitted by various insurance carriers and provides data about total payments (total costs to all payers) and payments made by patients (OOP costs) for their coinsurance, copayment, and/or deductible. 9 , 10 , 11 We identified enrollees aged 18 to 45 years with at least 1 full year of continuous enrollment from January 1, 2010, to December 31, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term healthcare utilization costs tend to be reduced due to more excellent proficiency with robotic surgery and a decline in Emergency room and office visits [ 21 ]. The main advantages of minimally invasive surgery for the patient are less pain medication use, quicker healing, better cosmesis, and fewer wound problems.…”
Section: Reviewmentioning
confidence: 99%